2022
DOI: 10.1039/d1cc05132f
|View full text |Cite
|
Sign up to set email alerts
|

An activator-induced quencher-detachment-based turn-on probe with a cationic substrate moiety for acetylcholinesterase

Abstract: We report a choline ester-grafted turn-on fluorescence probe to detect acetylcholinesterase (AChE) in living cells. AChE-mediated hydrolysis of the choline ester moiety producing carboxylate initiates the activation of Cy5 fluorophore...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…We subsequently performed kinetic studies of AChE with Naph-3 and found that Naph-3 serves as the best substrate ( K m = 7.5 μM) for AChE among the three probes tested (Figures C, S7, and Table S2, Supporting Information). Further, to the best of our knowledge, Naph-3 has the lowest K m for AChE among all the reported fluorogenic probes, suggesting that Naph-3 might serve as a better substrate for AChE compared to the reported probes (Table S3, Supporting Information). ,, …”
Section: Resultsmentioning
confidence: 85%
“…We subsequently performed kinetic studies of AChE with Naph-3 and found that Naph-3 serves as the best substrate ( K m = 7.5 μM) for AChE among the three probes tested (Figures C, S7, and Table S2, Supporting Information). Further, to the best of our knowledge, Naph-3 has the lowest K m for AChE among all the reported fluorogenic probes, suggesting that Naph-3 might serve as a better substrate for AChE compared to the reported probes (Table S3, Supporting Information). ,, …”
Section: Resultsmentioning
confidence: 85%
“…1a). Although 6- endo-trig cyclizations should be more favorable than 5- endo-trig , previous attempts at using 6- endo-trig cyclizations to impart fluorogenicity did not lead to more stable cyclic isomers 2730 . Based on these observations, we hypothesized that a 5- exo-trig cyclization would be a more efficient alternative.…”
Section: Resultsmentioning
confidence: 96%
“…Through the addition of nucleophilic side chains, however, several research groups have attempted to create fluorogenic polymethine dyes. The Ohe group decorated Cy5 and Cy7 dyes with alcohols, amines, and thiols as nucleophiles, thereby forming oxazines, diazines, and thiazines, respectively [27][28][29][30] . The Raymo group developed coumarin-hemicyanine hybrid fluorophores bearing a p-nitrophenol group that exists mainly in the spirocyclic form but can undergo a photoinduced and reversible interconversion into its open fluorescent form 24 .…”
Section: Mainmentioning
confidence: 99%
“…To evaluate the less‐emissive nature of the probe under neutral conditions, we defined R c value ( R c,abs ) [5b] that was obtained from UV–vis absorption spectra of βC5S‐A as the ratio of the non‐fluorescent closed‐ring form in a neutral buffered solution (pH 7.6) (Table 2). The R c,abs value was calculated using the following equation: Rc,abs=1-A7.6/A2.0 $\vcenter{\openup.5em\halign{$\displaystyle{#}$\cr R{_{{\rm c}{\rm \char44 }{\rm abs}}}=1- {\rm A}{_{7.6}}/{\rm A}{_{2.0}}\hfill\cr}}$ …”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no fragments are generated during the enzymatic reaction. By using the AiQd mechanism, turn‐on fluorescence probes for carboxyesterases, including acetylcholinesterase, [5b] and aldehyde dehydrogenase 1A1 (ALDH1A1) [5c,d] have been developed. In the case of ALDH1A1‐responsive probe C5S‐A , [5c] a formyl and mercapto group are grafted on a deep‐red cyanine dye Cy5 as an enzyme‐responsive substrate and a fluorescence‐quenching nucleophilic group, respectively (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%